2008
DOI: 10.1136/hrt.2007.140343
|View full text |Cite
|
Sign up to set email alerts
|

'Hypersynchronisation' by tissue velocity imaging in patients with cardiac amyloidosis

Abstract: The regional timing of systolic motion measured by TVI was abnormally synchronised in the patients with advanced-CA. ET reduction plays a prominent part in this process and should be considered an essential parameter for assessment of patients with cardiac amyloidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…7 This observation is similar to that of Migrino et al, 17 who used a longer follow-up period (median, 29 months) and a multivariate survival analysis that included biomarkers as well as clinical and standard echocardiographic variables. Ejection time ≤ 240 ms, NYHA class III or IV, and alkaline phosphatase levels were the only independent predictors of mortality in their group of patients with AL amyloidosis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…7 This observation is similar to that of Migrino et al, 17 who used a longer follow-up period (median, 29 months) and a multivariate survival analysis that included biomarkers as well as clinical and standard echocardiographic variables. Ejection time ≤ 240 ms, NYHA class III or IV, and alkaline phosphatase levels were the only independent predictors of mortality in their group of patients with AL amyloidosis.…”
Section: Discussionsupporting
confidence: 82%
“…Plasma BNP, NT-proBNP, and troponin T levels were measured as previously described. 7 To pool the data of the monoclonal kappa and lambda patients, the clonal free light chain was considered the “involved” immunoglobulin free light chain for the purpose of the analyses. Immunoglobulin clonal free light chain quantitation was carried out as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Echocardiography is an important noninvasive tool to assess cardiac involvement with classic findings of ventricular thickening and diastolic dysfunction with often preserved left ventricular ejection fraction 6-8. However, early systolic dysfunction is increasingly recognized with more sensitive techniques such as strain imaging 9, 10 and regional systolic dyssynchrony or hypersynchrony has recently been reported in AL subjects 11, 12. Prior retrospective studies of AL patients demonstrated prognostic value for echocardiography-derived abnormal deceleration time, ratio of peak early mitral inflow to late mitral inflow velocity (E/A ratio) as well as the Tei index that incorporates ejection time and isovolumetric relaxation/contraction time 13, 14.…”
mentioning
confidence: 99%
“…Prior retrospective studies of AL patients demonstrated prognostic value for echocardiography-derived abnormal deceleration time, ratio of peak early mitral inflow to late mitral inflow velocity (E/A ratio) as well as the Tei index that incorporates ejection time and isovolumetric relaxation/contraction time 13, 14. Recently, with a median follow up of 13 months, Bellavia and colleagues reported that the most important echocardiographic predictor of mortality was reduced left ventricular systolic ejection time (ET) although the underlying mechanistic basis behind the increased risk remains unknown 11. We hypothesized that standard echocardiographic structural, systolic and diastolic measures can identify AL patients at risk of dying on long-term follow up.…”
mentioning
confidence: 99%
“…This can easily be assessed by heart rate variability (HRV) studies [4], [5], [6]. Although autonomic disturbances are a well-established mechanism for reduced HRV [7], we hypothesize that cardiac function disturbances by themselves may have an additional impact on HRV -in a way similar to what was previously found in dilated cardiomyopathy [8] [9]. The aim of this study was, therefore, to assess the elationship between LV function and HRV in a cohort of Swedish patients with FAP.…”
Section: Introductionmentioning
confidence: 62%